Application Of The Small Group Discussion Model In Social Studies Learning For Class IV SD Negeri 57 Lubuklinggau - Hajani, Tri Juli; Sofiarini, Andriana; Munah, Mai (Widyagogik, 2023)
This study aims to determine the completeness of learning outcomes after the application of the Small Group Discussion Model in Class IV Social Studies Learning at SD Negeri 57 Lubuklinggau. The research method used is a quantitative method with quasi-experimental research in one group pre-test and post-test categories. The population of the entire fourth grade of SD Negeri 57 Lubuklinggau is 38 students and the sample or research subject is part of the population of 18 students. The technique of collecting data is by using a test in the form of an essay. The data analysis technique used the "t" test formula, based on the results of hypothesis testing, it was obtained thitung = 7,45 and ttabel with degrees of freedom dk = 18-1 = 17 and = 0.05 obtained ttabel = 1.74, then thitung 7,45 ttabel 1.74 which means Ho is rejected and Ha is accepted. So it can be concluded that the learning outcomes of fourth grade students at SD Negeri 57 Lubuklinggau after the implementation of the Small Group Discussion Model on social studies learning are significant.